2020
DOI: 10.1099/jmm.0.001101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antifungal susceptibility profiles of clinical Cryptococcus neoformans/Cryptococcus gattii species complex

Abstract: The sequences from the isolates determined in current study has been deposited in GenBank under the accession number from MK591061 to MK591074.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
1
6
0
2
Order By: Relevance
“…Although C. neoformans and C. deuterogattii clinical isolates have presented MIC above ECV for FLU, ITR and VOR, most of the clinical isolates are wild‐type to these antifungal drugs. Similarly, most of the C. neoformans clinical isolate from Brazil and other countries have been shown to be wild‐type strain to FLU, ITR and VOR (MIC below the ECV) 13,17,33,34,36,37 . The MICs of 5‐FC for all clinical isolates in our study were within the wild‐type range, which has been found for C. neoformans and C. deuterogattii clinical isolates from the southern and south‐eastern region of Brazil 13,33,34,36 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although C. neoformans and C. deuterogattii clinical isolates have presented MIC above ECV for FLU, ITR and VOR, most of the clinical isolates are wild‐type to these antifungal drugs. Similarly, most of the C. neoformans clinical isolate from Brazil and other countries have been shown to be wild‐type strain to FLU, ITR and VOR (MIC below the ECV) 13,17,33,34,36,37 . The MICs of 5‐FC for all clinical isolates in our study were within the wild‐type range, which has been found for C. neoformans and C. deuterogattii clinical isolates from the southern and south‐eastern region of Brazil 13,33,34,36 .…”
Section: Discussionsupporting
confidence: 79%
“…Our results are in line with most of Cryptococcus spp. isolates since the emergence of HIV, which are mostly wild‐type to AMB 13,17,33,34,36,37 . Therefore, the majority of C. neoformans VNI isolates are currently wild‐type concerning AMB.…”
Section: Discussionmentioning
confidence: 99%
“…Bandalizadeh et al in their study reported the mortality rate of CM to be 64%. The higher mortality rate in the study of Bandalizadeh et al may be due to the more severe immunodeficiency condition of patients and also the lack of access to the use of flucytosine in the first-line treatment in combination with amphotericin B [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous species of Cryptococcus , C. neoformans and C. gattii species complexes are the major causative agents of human cryptococcosis [ 7 ]. Measurement of cryptococcal antigen (Ag) titer and/or culture are the mainstay for a definite diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cases caused by C. neoformans are observed worldwide, but cases caused by C. gattii are not frequently observed globally. In addition, C. gattii exhibits relatively higher resistance to antifungal drugs, while both C. gattii and C. neoformans have been recognized as having different degrees of resistance to certain antifungal drugs, such as azoles ( 5 , 6 ). The differences in epidemiology and drug resistance exhibited by C. gattii may be attributable to different pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%